Generalizing Action Justification and Causal Links to Policies - Sreedharan, Sarath; Muise, Christian; Kambhampati, Subbarao (Proceedings of the International Conference on Automated Planning and Scheduling, 2023)
We revisit two concepts popularly used within the context of classical planning, namely action justification and causal links. While these concepts have come to underpin some of the most popular notions of explanations in classical planning, these notions are restricted to sequential plans. To address this shortcoming, we propose a generalization of these concepts that is applicable to state-action policies. We introduce algorithms that can identify justified actions and causal links contributed by such actions for policies generated for Fully Observable Non-Deterministic (FOND) planning problems. We also present an empirical evaluation that demonstrates the computational characteristics of these algorithms on standard FOND benchmarks.